Optimalisasi Proses Pengelasan di Bengkel Sumber Rejeki Malang dengan Teknologi Gas Tungsten Arc Welding: Optimization of the Welding Process at Sumber Rejeki Workshop Malang using Gas Tungsten Arc Welding Technology - Sudarman, Sudarman; Sabariman, Rizky Wahyu; Buludatu, Riski; Muzaky, Muhammad Azriel; Alam, Adi Bahrul; Setiawan, Hendra Agus; Nugroho, Willy Satrio; Sofi'i, Yepy Komaril (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Sumber Rejeki Welding Workshop is one of the small and medium enterprises engaged in manufacturing and welding services in Malang City. In its production process, the workshop still relies on conventional welding methods that are less efficient and produce suboptimal weld quality. Therefore, this community service program aims to enhance production efficiency and quality by implementing Gas Tungsten Arc Welding technology and assisting in applying occupational health and safety standards. The implementation method of this program includes several stages: the preparation stage, which involves identifying partner needs and machine installation; the training stage, consisting of theoretical and practical sessions for operators; the production assistance stage; and the evaluation stage, using the Non-Destructive Testing method with penetrant testing techniques to assess weld quality. The results of this program implementation indicate a 30% improvement in production efficiency, with reduced processing time and fewer welding defects. Significant economic impacts are also evident through increased production capacity and the workshop's competitiveness in the local market. Furthermore, the provided training has enhanced the operators' skills in machine operation and raised their awareness of the importance of occupational safety standards. This program demonstrates that adopting modern welding technology can significantly improve productivity and product quality, making it a potential model for application in other small and medium enterprises to boost competitiveness in the manufacturing sector.